2018
DOI: 10.14202/vetworld.2018.104-111
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and quantification of Shiga toxin-producing Escherichia coli from food matrices

Abstract: Aim:The objective of the study was to detect Shiga toxin-producing Escherichia coli (STEC) and develop a quantitative polymerase chain reaction (qPCR) assay to quantify the bacterial DNA present in different food matrices.Materials and Methods:A total of 758 samples were collected during a period from January 2015 to December 2016 from Kozhikode, Thrissur, and Alappuzha districts of Kerala. The samples consisted of raw milk (135), pasteurized milk (100), beef (132), buffalo meat (130), chevon (104), beef kheem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…our results demonstrate that the percentage of E. coli isolated from meat and butcher shops was 27.4% (138/504). In addition, this study showed the percentage of E. coli was rising in meat at 41.7% (35/84), which agreed with the previous surveys that found the percentage of E. coli in meat was 43.1% in India (23), 43.4 % in the United States (24). However, our results are lower than the previous surveys that appeared the percentage of E. coli from meat in Egypt was 54% (27/50) (25), 74.5% in South Africa (26), and 100% in Burkina Faso (27).…”
Section: Discussionsupporting
confidence: 92%
“…our results demonstrate that the percentage of E. coli isolated from meat and butcher shops was 27.4% (138/504). In addition, this study showed the percentage of E. coli was rising in meat at 41.7% (35/84), which agreed with the previous surveys that found the percentage of E. coli in meat was 43.1% in India (23), 43.4 % in the United States (24). However, our results are lower than the previous surveys that appeared the percentage of E. coli from meat in Egypt was 54% (27/50) (25), 74.5% in South Africa (26), and 100% in Burkina Faso (27).…”
Section: Discussionsupporting
confidence: 92%
“…In Iran, a study was conducted by Mohammadi et al (2013) who found that the prevalence of STEC in raw milk was 17.47 % (36 out of 206 samples). More or less similar results were reported in previous studies by Abadu et al (2020) andSethulekshmi et al (2018) who found that the prevalence of STEC in raw milk samples were, 19% and 19.26%, respectively. Moreover, similar results were recorded in Germany byZschock et al, (2000) who stated that STEC in raw milk was 18%.…”
supporting
confidence: 91%
“…STEC causes many infections in humans, including gastrointestinal illnesses including non-bloody or bloody diarrhea, hemorrhagic colitis, and hemolytic uremic syndrome [ 53 ], which has been infrequently identified in camels. The transmission of STEC usually occurs through contaminated foods, water, and person-to-person spread [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%